Comparison of different orders optimization using Continuous Genetic Algorithm “THIS PAPER HAS BEEN WITHDRAWN” - Yadav, Vijay; Bhadauria, S.S. (International Journal of Engineering and Technology, 2012)
“THIS PAPER HAS BEEN WITHDRAWN”